Evaluation and calculations of modes resonant cantilever for laser optical fiber assembly - Mohanad H. Ali (Institute of Advanced Engineering and Science, 2020)
Biosensors depend on cantilevers have developed a promising tool for detecting biomedical, optical laser communication and many fields of interactions with high accuracy. We modeled the operation of cantilevers with two magnetic and coil using Ansys program. This simulation technique can capably be used to select the appropriate design and dimensions of cantilever with the geometry of system. The primary main of the magnetic design is to improve the geometry of the coil and shape to yield a highly uniform for 3D of optical fiber includes Silica Glass and Nickel cantilever, two magnets and one coil that apply to force on the cantilever cylinder is using as a cantilever in the designing of this case.In conclusion,resonant frequency( tuning applying cantilivier presented in the resracher have larger variable range by using 2-magnets with the coil.However,the adjusting of the system and changing the deminsions.Resolutions to this problematic contain tuning the modes of resonant frequency to produce by cantilivier with 2-magnets and coil when the signal pass from laser source. Based on these simulations and characterization results, the proposed assembly can be a good applicant for evolving a low price, high material platform for many biological, laser optical fiber, communication, machine learning, biosensors and biomedical applications.